2019
DOI: 10.5858/arpa.2017-0495-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of Coexisting Activating Mutations Within EGFR, Mitogen-Activated Protein Kinase, and Phosphatidylinositol 3-Kinase Pathways in Lung Cancers

Abstract: Context.-Mutations within the same signature transduction pathway are redundant and, therefore, most are mutually exclusive. Laboratory errors, however, may introduce unexpected coexisting mutations. Objective.-To validate coexisting mutations within epidermal growth factor receptor (EGFR), mitogen-activated protein kinase, and phosphatidylinositol 3-kinase pathways. Design.-In this retrospective study for quality assessment of next-generation sequencing in a clinical diagnostics setting, coexisting mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…26 These trunk drivers are usually mutually exclusive, although rare cases with coexisting EGFR and KRAS mutations have been reported. 27 In contrast, TP53 and PIK3CA mutations are branching drivers and can be seen in BRAF-, EFGR-, or KRAS-mutated lung adenocarcinomas. In a total of 25 IDH1/2-mutated lung adenocarcinomas reported by Toth et al, TCGA, MSK-IMPACT, and this study, known trunk F I G U R E 4 Correlation of variant allele frequency (VAF).…”
Section: Discussionmentioning
confidence: 99%
“…26 These trunk drivers are usually mutually exclusive, although rare cases with coexisting EGFR and KRAS mutations have been reported. 27 In contrast, TP53 and PIK3CA mutations are branching drivers and can be seen in BRAF-, EFGR-, or KRAS-mutated lung adenocarcinomas. In a total of 25 IDH1/2-mutated lung adenocarcinomas reported by Toth et al, TCGA, MSK-IMPACT, and this study, known trunk F I G U R E 4 Correlation of variant allele frequency (VAF).…”
Section: Discussionmentioning
confidence: 99%
“…The Akt1 mutation is rare in lung cancer with a total reported frequency of 0.6–5.5%, and studies to date have found that the E17K mutation is mainly expressed in the lung epithelium and that the mutation may be present only in squamous cell carcinoma in non-small cell lung cancer (Bleeker et al, 2008 ; Do et al, 2008 ; Kim et al, 2008 ; Malanga et al, 2008 ; Rekhtman et al, 2012 ; De Marco et al, 2015 ; De Marchi et al, 2019 ). The AKT1(E17K) mutation promotes migration and invasion of human lung epithelial cells, enhancing their oncogenic and metastatic potential (De Marco et al, 2015 ).…”
Section: The Effects Of Akt E17k Mutation Across Various Tumorsmentioning
confidence: 99%
“…Unexpectedly, ALK patients had a low OS, perhaps due to the unavailability of TKIs as first-line treatment at the beginning of the study and to the coexistence of KRAS mutation in three of the nine ALK patients. This occurrence is rare, but it has already been reported as being associated with primary resistance to TKIs [32,33]. The expected co-occurrence of TP53 mutations with KRAS, EGFR, BRAF , PIK3CA , and STK11 were also identified.…”
Section: Discussionmentioning
confidence: 78%